2021
DOI: 10.51850/jitkt.v17i2.473
|View full text |Cite
|
Sign up to set email alerts
|

Sifat Fisis dan Mekanis Oriented Strand Board Hibrida Bambu Pada Berbagai Shelling Ratio (Physical and Mechanical Properties of Hybrid Bamboo Oriented Strand Board at Various Shelling Ratios)

Abstract: Hybrid Bamboo Oriented Strand Boards (OSB) were produced to improve bamboo OSB's physical and mechanical properties. Shelling ratio adjustment of the strand type combination could determine the optimal physical and mechanical properties of hybrid bamboo oriented strand boards (OSB). The purpose of this study was to evaluate the physical and mechanical properties of hybrid betung and andong bamboos OSB at various shelling ratios. Steam modified strands of betung and andong bamboo were used as an outer layer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 1 publication
1
9
1
3
Order By: Relevance
“…Nevertheless, the SHP values of bamboo-based OSB in this study were lower than those reported in a previous study by Hidayat et al (2013). This situation is possibly due to the use of low-density wood raw materials, i.e., Paraserianthes falcataria (0.36 g/cm 3 ), Maesopsis eminii (0.41 g/cm 3 ), and Acacia mangium (0.46 g/cm 3 ) in the OSB manufacture, which resulted in higher compression ratio to meet the targeted OSB density (0.70 g/cm 3 ).…”
Section: The Screw-holding Powercontrasting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the SHP values of bamboo-based OSB in this study were lower than those reported in a previous study by Hidayat et al (2013). This situation is possibly due to the use of low-density wood raw materials, i.e., Paraserianthes falcataria (0.36 g/cm 3 ), Maesopsis eminii (0.41 g/cm 3 ), and Acacia mangium (0.46 g/cm 3 ) in the OSB manufacture, which resulted in higher compression ratio to meet the targeted OSB density (0.70 g/cm 3 ).…”
Section: The Screw-holding Powercontrasting
confidence: 93%
“…The values of MOE parallel to the surface grain of bamboo OSBs in this study were comparable to those of OSBs prepared from four different Canadian wood species (balsam fir, trembling aspen, black spruce, and jack pine) (Zhuang et al 2022b). However, their values were higher than those of OSB prepared from the mixture of Calophyllum inophyllum's and Paulownia coreana's strands that were glued with synthesized phenolformaldehyde and phenol-urea-formaldehyde (Oh and Kim 2015), OSB prepared from CCB treated fast-growing tree species strands (Hidayat 2013), OSB prepared from steamtreated bamboo strands (Febrianto et al 2015), and OSB prepared from resinous and broadleaved fast-growing species (Lunguleasa et al 2021). These differences may be due to different processing parameters used during the OSB manufacture from each previous study mentioned above.…”
Section: The Moementioning
confidence: 88%
See 1 more Smart Citation
“…Kayu sengon (Falcataria moluccana) adalah salah satu jenis kayu tropis cepat tumbuh yang ada di Indonesia (Hidayat et al, 2011). Sengon merupakan salah satu jenis tanaman yang paling dimanfaatkan di daerah tropis (Iskandar, 2006).…”
Section: Pendahuluanunclassified
“…Logs derived from private forests serve as a primary wood resource for the small-scale sawmill sector (Syah et al 2018;Utama et al 2019). Furthermore, it has been observed that logs derived from sengon (Hidayat et al 2017;Utama et al 2019) are frequently employed in many sectors, such as the bare core industry, plywood manufacturing, laminated veneer lumber production, and container industry. The harvesting residue, which is a byproduct of harvesting operations, plays a significant part in the practice of sustainable forest management.…”
Section: Introductionmentioning
confidence: 99%